Retinal neurovascular alteration in type 2 diabetes with renal impairment in association with systemic arterial stiffness - Sauli Ari Widjaja; William F. Mieler; Wimbo Sasono; Soebagijo A. Soelistijo; Arief S. Kartasasmita; Akira Murakami; Shintaro Nakao (International Journal of Retina and Vitreous, 2024)
Abstract Background Diabetic retinopathy (DR) patients should be alert for subclinical macroangiopathy. We aimed to investigate the association between retinal neurovascular alteration and systemic arterial stiffness in type 2 diabetes mellitus (type 2 DM) patients with varying degrees of renal impairment. Methods The study included 170 patients with confirmed diagnosis of type 2 DM aged ≥18 years old. Renal function was assessed by estimated glomerular filtration rate (eGFR). Arterial stiffness was measured by brachial-ankle pulse wave velocity (baPWV) and ankle brachial index (ABI). Retinal neurovascular parameters were derived from Optical Coherence Tomography (OCT)/OCT-Angiography, represented by vessel density (VD Central, Inner, Outer, Full), foveal avascular zone (FAZ area and FAZ perimeter) of the superficial capillary plexus, the average of macular ganglion cell-inner plexiform layer thickness (ave mGC-IPLt) and the average of retinal nerve fiber layer thickness (aveRNFLt). The association between variables among the groups (according to renal function, diabetic retinopathy (DR) severity, and arterial stiffness categories) were analyzed by regression analysis with multiple hypothesis testing commands. Results Out of the 265 eyes, the mean DM duration and HbA1c were 6.21 ± 6.37 years and 8.44 ± 2.06% respectively. While the mean of eGFR, baPWV and ABI were 66.78 ± 32.80 ml/min/1.73m2, 15.49 ± 3.07 m/s, and 1.05 ± 0.12, respectively. Patients with more severe renal impairment demonstrated longer DM duration (p < 0.001), higher baPWV (p < 0.0001), and retinal vascular alteration. Proliverative DR group showed the lowest eGFR (p < 0.0001), highest baPWV (p < 0.0001), and retinal neurovascular changes. Significantly lower eGFR and retinal vascular alteration were found in the baPWV > 14 group. Some neurovascular parameters were significantly negatively correlated with baPWV; moreover, retinal neurovascular changes were also noted in the abnormal ABI group. Conclusions The strong association between changes in the retinal neurovascular system, DR severity, renal impairment, and arterial stiffness in type 2 DM was confirmed. Patients with more severe renal impairment had higher levels of arterial stiffness, more severe DR and retinal neurovascular alteration. Retinal neurovascular changes seen in OCT/OCTA might mimic renal microvascular alteration and systemic arterial stiffness. Therefore, assessment of baPWV and OCT/OCTA should be integrated in DR screening to enhance cardiovascular risk stratification and prognosis as well as to provide clinically useful early identification of subclinical micro- and macrovascular alterations.